Ion Exchange Properties of Crosslinked and Carboxylated Peanut (Arachis Hypogaea L.) Testa Extract (British Journal of Multidisciplinary and Advanced Studies, 2023)
After polymerization via polycondensation of catechin units in the acetone extract of peanut (arachis hypogaea L.) testa (PTE) using phosphorus oxychloride (POCl3) as a crosslinking agent, POCl3-crosslinked PTE (Crosslinked-PPTE) was functionalized by etherification (PC-PTE) using monochloroacetic acid (MCAA) in the presence of an alkali according to the method of Williamson ether synthesis. Subsequent to characterization by Fourier Transform Infrared spectroscopy (FTIR) as well as physical properties, Crosslinked-PPTE was assessed for cation exchange capacity (CEC) and pH at point of zero charge (ZPHC) following demonstrated capacity to remove heavy metal ions in single and multi-elements aqueous solutions by Atomic Absorption Spectrometry (AAS) technique while functionalized (carboxymethylated) Crosslinked-PPTE (PC-PTE) was further characterized by degree of substitution (DS). FTIR absorption bands due to -C-O-P=O, -P=O, P-O-C- and R-O-P-OH stretching vibrations were seen at 1350/1250, 1244/1246, 997/993 cm-1 respectively. Asymmetric and symmetric stretching vibrations of the -C=O of a COOH, Ar-O-C- of an aromatic ether as well as -P-O-C - of an aromatic PO43-, R-P=O of a -PO43-, -R-O-P- and R-O-P-OH of a PO43- ester created by crosslinked and carboxymethylated PTE respectively were seen at 1743, 1377, 1278, 1190, 1062 and 823 cm-1. The results obtained showed that 0.6 was the DS of PC-PTE while 6.72 meq/g and 3.57 defined the CEC and pH (zpc) respectively of Crosslinked-PPTE. Quantitative removal of Fe2+, Ni2+, Pb2+, Cu2+ and Zn2+ in laboratory simulated metal ion wastewater (LSW) to the levels of 84.4, 81.7, 76.5, 72.0 and 75.1% respectively was achieved using Crosslinked-PPTE resin in batch adsorption experiments in which the efficiency was found to depend significantly on the temperature and pH of the water as well as initial adsorbate concentration and contact time but partially on the amount of adsorbent used was observed to be independent of the speed of stirring of the wastewater. Stable, Matakana and fine powder crosslinked-PPTE which is insoluble in water and common laboratory solvents holds great potential in the purification of heavy metal ions polluted water